Pengaruh Disiplin Kerja Terhadap Kinerja Guru MTs Se- Kota Bandar Lampung - Hadiati, Eti (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2018)
Teachers’ performance is one of the factors that is necessary to organize theexcellent education and learning. Teachers’ performance improvement effortis influenced by many factors, including discipline of work. The problem isdiscipline of work is not be a culture of school academic. The method used inthis research was a quantitative method with survey approach and thelocation of this reserch is at MTs around Bandar Lampung with 82 personsof respondences chosen as the sample. Research result shows that disciplineof work has a positive effect and significant to teachers’ performance of theMts around Bandar Lampung.